2018
DOI: 10.2147/ceg.s153924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistant maltodextrin on bowel movements: a systematic review and meta-analysis

Abstract: It is well known that dietary fiber helps to relieve and prevent constipation, and there are a number of scientific papers, including systematic reviews and meta-analyses on the effects of naturally derived dietary fiber on bowel movements. In recent years, there has been an increase in the manufacture of dietary fiber ingredients obtained from food raw materials, and these are now commonly available in the market. Resistant maltodextrin (RMD), a soluble dietary fiber, is manufactured from starch, and industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Non-digestible and functional carbohydrates are commonly referred to as dietary fiber, which provide health benefits such as intestinal motility (Watanabe et al 2018) and intestinal immune functions (Fastinger et al 2008;Miyazato et al 2016). Heating starch, occasionally with acid, causes a modification of polymer structures, thus resulting in different characteristics such as solubility in cold water, decreased viscosity, and resistance to alpha-amylase.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Non-digestible and functional carbohydrates are commonly referred to as dietary fiber, which provide health benefits such as intestinal motility (Watanabe et al 2018) and intestinal immune functions (Fastinger et al 2008;Miyazato et al 2016). Heating starch, occasionally with acid, causes a modification of polymer structures, thus resulting in different characteristics such as solubility in cold water, decreased viscosity, and resistance to alpha-amylase.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The appropriate intake of the soluble and insoluble dietary fiber ensures multiple health benefits both in the prophylaxis and treatment of many diseases [ 17 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Dietary fiber and its resistant starch fraction are nutrients for the symbiotic intestinal flora; they stimulate its growth (e.g., in the case of Ruminococcus bromii , bifidobacteria, and lactobacilli) while inhibit the growth of opportunistic or pathogenic microorganisms (e.g., clostrnidium) [ 66 , 73 , 74 ].…”
Section: Starch Citrates As Resistant Starchmentioning
confidence: 99%
“…Fermentation of dietary fiber leads to the formation of short chain fatty acids (SCFAs), i.e., butyric acid, propionic acid, valeric acid, isovaleric acid, and hexanoic acid [ 73 , 75 ]. A higher content of SCFAs decreases the pH value of colonic digesta [ 66 , 68 ], enhances mucin synthesis, ensures better tightness of the intestinal barrier [ 63 , 71 ], regulates the composition and numbers of intestinal microflora, reduces the inflammatory conditions (e.g., in kidneys of type 2 diabetic patients) [ 71 ], and enhances vitamin D3 synthesis [ 68 , 71 ]. The mentioned properties of fiber have also been confirmed in the case of the citrate that consist of the RS4 type of starch.…”
Section: Starch Citrates As Resistant Starchmentioning
confidence: 99%
“…In general, fiber supplements are recommended to increase the fiber consumption of constipation patients. However, recent clinical studies have reported that high fiber diets, especially those in which the fiber is consumed as supplements, can cause intestinal discomfort such as convulsive abdominal pain and gas production, and even constipation or fecal impaction [6][7][8][9]. In addition, several systematic reviews and meta analyses have reported that although dietary fiber increased the number of bowel movements in constipation patients, it was unclear whether it improved fecal consistency [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent clinical studies have reported that high fiber diets, especially those in which the fiber is consumed as supplements, can cause intestinal discomfort such as convulsive abdominal pain and gas production, and even constipation or fecal impaction [6][7][8][9]. In addition, several systematic reviews and meta analyses have reported that although dietary fiber increased the number of bowel movements in constipation patients, it was unclear whether it improved fecal consistency [6,8,9]. Previous reports have discussed the relevance of fiber supplements to complement a lack of natural dietary fiber intake, such as resistant maltodextrin, beta-glucan, psyllium, inulin, cellulose, and konjac glucomannan, to bowel movements [7,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%